Sensitivity study on Virginia fanpetals (Sida hermaphrodita (L.) RUSBY) cv PETEMI to different herbicide agents - Szabó, Béla; Szabó, Miklós; Papp, Roland; Kárpát, Zoltán; Vágvölgyi, Sándor (Acta Agraria Debreceniensis, 2010)
The cultivation of Virginia fanpetals (Sida hermaphrodita (L.) Rusby) is a relatively new phenomenon in Europe. On the basis of the biology of the plant and the practical work implemented, it has been stated that the traditional field practice does not provide the appropriate conditions of biomass production for energetic purpose. The development of the proper weed control is inevitable for the healthy stand, as in the early phenophases the plant is growing slowly and it is exposed to weeds. Our objective was to test some herbicide agents as no previous relevant data had been published.